PD-L1 knockout or ZG16 overexpression inhibits PDAC progression and modulates TAM polarization - Meng, Hui; Nan, Manman; Li, Yizhen; Ding, Yi; Fang, Xiaokun; Ma, Weiqian; Zhang, Mingzhi (Frontiers in Immunology, 2025)
CRISPR/Cas9-mediated genome editing has the potential to delete PD-L1 both on the cell surface and inside the cell, thereby inhibiting tumor growth and migration and overcoming immunosuppression. ZG16, with its lectin structure, can reduce PD-L1 expression on the cell surface. However, direct comparison of two approaches on PD-L1 expression in Pancreatic ductal adenocarcinoma (PDAC) cells has not yet been investigated. In this study, we established two Panc-1 cell line: one with PD-L1 knockout and another with ZG16 overexpression. Both methods promoted the polarization of tumor-associated macrophages (TAMs) to the M1 phenotype, as indicated by increased levels of the M1 marker CD11c+ in vitro and in vivo. Meanwhile, we observed a reduction in the M2 marker CD206+, upregulation of immune activation-related cytokines/chemokines, and a decrease in immunosuppressive cytokines and tumor angiogenesis factors. In summary, both PD-L1 knockout and ZG16 overexpression represent promising approaches for PDAC treatment.